Influence of the different stress paths on rock deformation memory effects using the deformation rate analysis method - Zhong, Lingwei; Ren, Xuhua; Wang, Haijun; Zhao, Guangchuan; Li, Yang; Zhu, Jiawei (Frontiers in Earth Science, 2024)
Deformation memory effect (DME) is a common property of the rock. A method called Deformation Rate Analysis (DRA) which is based on DME provides a brand-new approach to measuring in situ stress. When rock DME is applied in engineering, it is necessary to solve the problem that which stress peak is corresponding to in situ stress. The standard square samples made of sandstone and granite were selected to investigate the rock DME under different stress paths. Then a memory theoretical model based on multi-surface sliding friction hysteresis is used to analyze the mechanisms of rock DME. The results show that: (1) Rocks always remember the maximum peak stress from preloading, regardless of the sequence of multiple preloading; (2) Multi-memory exists in tests because we found another inflection in DRA curve; (3) The memory model based on sliding friction hysteresis shows the precision of memory information formation increases as the historical maximum peak value gets closer to the measurement load, but multi-memory does not exist in theoretical analysis. The conclusion provides the rule of rock DME under different stress path which would benefits in in situ stress reconstruction.